Lignin‐Derived Thioacidolysis Dimers: Reevaluation, New Products, Authentication, and Quantification. Issue 5 (15th February 2017) - Yue, Fengxia; Lu, Fachuang; Regner, Matt; Sun, Runcang; Ralph, John
Abstract: Lignin structural studies play an essential role both in understanding the development of plant cell walls and for valorizing lignocellulosics as renewable biomaterials. Dimeric products released by selectively cleaving β–aryl ether linkages between lignin units reflect the distribution of recalcitrant lignin units, but have been neither absolutely defined nor quantitatively determined. Here, 12 guaiacyl‐type thioacidolysis dimers were identified and quantified using newly synthesized standards. One product previously attributed to deriving from β–1‐coupled units was established as resulting from β–5 units, correcting an analytical quandary. Another longstanding dilemma, that no β–β dimers were recognized in thioacidolysis products from gymnosperms, was resolved with the discovery of two such authenticated compounds. Individual GC response factors for each standard compound allowed rigorous quantification of dimeric products released from softwood lignins, affording insight into the various interunit‐linkage distributions in lignins and thereby guiding the valorization of lignocellulosics. Abstract : A closer look at lignin structures : New insights are gained from authenticating and quantifying dimeric thioacidolysis products using various synthesized standard guaiacyl‐type dimers. A longstanding compound assignment error is corrected, the dilemma of observing no β–β products from pinoresinol structures from softwood lignins is resolved, and the combinatorial nature of lignification is confirmed.